Acute tryptophan depletion promotes an anterior‐to‐posterior fMRI activation shift during task switching in older adults. Issue 2 (20th December 2012) - Lamar, Melissa; Craig, Michael; Daly, Eileen M.; Cutter, William J.; Tang, Christine; Brammer, Michael; Rubia, Katya; Murphy, Declan G.M.
<x xml:space="preserve">Abstract</x> Studies have long reported that aging is associated with declines in several functions modulated by the prefrontal cortex, including executive functions like working memory, set shifting, and inhibitory control. The neurochemical basis to this is poorly understood, but may include the serotonergic system. We investigated the modulatory effect of serotonin using acute tryptophan depletion (ATD) during a cognitive switching task involving visual‐spatial set shifting modified for a functional MRI environment. Ten healthy women over 55 years were tested on two separate occasions in this within‐group double‐blind sham‐controlled crossover study to compare behavioral and physiological brain functioning following ATD and following a ("placebo") sham depletion condition. ATD did not significantly affect task performance. It did modulate brain functional recruitment. During sham depletion women significantly activated the expected task‐relevant brain regions associated with the Switch task including prefrontal and anterior cingulate cortices. In contrast, following ATD participants activated posterior regions of brain more during switch than repeat trials. In addition to the main effects of depletion condition, a comparison of the ATD relative to the sham condition confirmed this anterior‐to‐posterior shift in activation. The posterior (increased) activation clusters significantly and negatively correlated with the reduced prefrontal activation clusters suggesting a compensation mechanism for reduced prefrontal activation during ATD. Thus, serotonin modulates an anterior‐to‐posterior shift of activation during cognitive switching in older adults. Neural adaptation to serotonin challenge during cognitive control may prove useful in determining cognitive vulnerability in older adults with a predisposition for serontonergic down‐regulation (e.g., in vascular or late life depression). Hum Brain Mapp 35:712–722, 2014. © 2012 Wiley Periodicals, Inc.